What Is a Family? Answers from Early Modern Japan - Berry, Mary Elizabeth; Yonemoto, Marcia (University of California Press, 2019)
What is a family? The essays gathered here explore disparate family histories in early modern Japan, attending variously to the samurai elite, agrarian villagers, urban merchants, communities of outcastes, and the circles surrounding priests, artists, and scholars. They draw on diverse sources-from population registers and legal documents to personal letters and diaries, from genealogies and necrologies to popular fiction and drama. And while some examine collective practices (the adoption of heirs, the veneration of ancestors), others look intimately at individual actors (a runaway daughter, a murderous wife). What unites these stories is the political and social order of the Tokugawa shogunate (1603-1868), which structured all lives. Families navigated its constraints differently, but the circumstances that made one household unlike another were framed, then as now, by prevailing laws, norms, and controls on resources. Those constraints led the majority to form stem families, the focus of this volume. The essays nonetheless depart from essentialist and nationalist narratives to emphasize that family formation was a dynamic process mediated by particular pressures.